Characterizing dislocation structure evolution during cyclic deformation using electron channelling contrast imaging - Ahmed, J; Roberts, S; Wilkinson, A (2006)
This paper briefly reviews development of the electron channelling contrast imaging (ECCI) technique, which uses diffraction contrast to reveal dislocation structures underlying the surface of bulk samples imaged in the scanning electron microscope. In particular, the application of ECCI to the study of evolution of dislocation structures during cyclic deformation of single crystal copper samples will be described. Quantitative measurements of the vein width, separation and volume fraction within the matrix phase were made and these parameters showed rapid changes during the initial cyclic hardening of the sample, with smaller variations continuing after stress saturation. The volume fraction of persistent slip bands (PSBs) increased continuously with cycling beyond stress saturation. Measurements of PSB widths and spacings indicated that new PSBs tend to form near existing PSBs. The ECCI technique revealed PSBs of finite length with tapered ends. Stress concentrations occurring ahead of the tapered PSBs may be the cause of preferential nucleation of new PSBs close to existing ones.